2019
DOI: 10.1504/jgba.2019.099918
|View full text |Cite
|
Sign up to set email alerts
|

Twitter analysis of founders of top 25 Indian startups

Abstract: With the recent growth in social media dominance over the internet, many people have turned to these media to share their personal views, express their opinions and interact socially. This paper examines the social media content of Indian Chief Executive Officers who are the founders or co-founders of the top 25 Indian startups. The active involvement of Chief Executive Officers in social media influences the business effectiveness, performance and market legitimacy of the business. Social media has now become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Social networks reflect the importance and impact of this specific area of Indian startups. In this respect, our results are consistent with those reported by Sindhani [27] too. Furthermore, our results showed that technologies such as artificial intelligence and augmented reality were also positively discussed on Twitter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Social networks reflect the importance and impact of this specific area of Indian startups. In this respect, our results are consistent with those reported by Sindhani [27] too. Furthermore, our results showed that technologies such as artificial intelligence and augmented reality were also positively discussed on Twitter.…”
Section: Discussionsupporting
confidence: 93%
“…In their analysis aimed at the identification of innovation factors in Indian startups, Dinesh and Sushil [26] underscored the importance of creativity and innovation for the success of startups strategies. In a case study in the field of social media, Sindhani [27] analyzed 25 top Indian startups to identify the indicators startup founders should follow to develop strategies in this digital environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Singh et al (2019) examined tweets from startup founders and revealed that their key topics included digital technologies, e-commerce platforms, and consumer experiences. Sindhani et al (2019) investigated startup CEOs’ tweets and identified their significant themes: business situations, personal emotions, and societal issues. Peixoto et al (2023) analyzed tweets of Portuguese IT startups and identified five topics including FinTech, product/service R&D, and funding.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, SNS are reportedly crucial for the success and even survival of startups (Banerji & Reimer, 2019; Gloor et al, 2020). The research focus, however, has been placed more on the SNS accounts of founders or CEOs of startups (Sindhani et al, 2019; Yue et al, 2019) than on organizational accounts, and there has been scant research on the characteristics of posts on startups’ SNS accounts.…”
mentioning
confidence: 99%
“…The influence of amount of content posted on SM on firm performance has been studied widely. It has been found that increased usage of SM leads to firm's achieving higher IPO valuations (Mumi et al, 2019), increased brand equity (Sindhani et al, 2019), better financing outcomes and venture capital funding (Aggarwal et al, 2012;Albrecht et al, 2019;Wang and Wu, 2019), helps in matching investors with the start-ups (Prokofieva and Miah, 2020), etc. Overall, these studies suggest that SM usage influences firm performance, including the success of start-ups and their ability to obtain financing.…”
Section: Social Media Activitymentioning
confidence: 99%